Effects of climate shocks on Ethiopian rural households: an integrated livelihood vulnerability approach. Issue 3 (23rd February 2021) - Endalew, Haron Agegnehu; Sen, Subir
Abstract : The rural households engaged in the primary sector are vulnerable to climate shocks. The adaptation strategies are supposed to be locale specific, determined by biophysical and socio-economic factors and adoption is contingent on the results from vulnerability assessments. This study is an assessment of local level vulnerability of three heterogeneous groups of selected rural households in South Gondar zone in Ethiopia's Amhara region. The study analyses the effects of climate change induced shocks on livelihoods using the LVI-IPCC framework along with an econometric technique to determine factors responsible for variations across households. The study corroborates earlier results that rural households are adversely impacted by climate shocks. The poor non-off-farm diversified rural households are highly vulnerable in comparison to those households adopting an off-farm diversification strategy. Irrigation, improvements in access to water, health and other rural infrastructure are also factors reducing vulnerability.